Báo cáo tóm tắt tình hình hoạt động ngành công nghiệp và thương mại tháng 8 và 8 tháng năm 2007 - Bộ Công thương (2007)
Báo cáo tóm tắt tình hình hoạt động ngành công nghiệp và thương mại tháng 8 và 8 tháng năm 2007.